Comparisions of Efficiency Wood Pellet Mill between D-type and R-type - เทพษร, พงศกรณ์; ศรีรักษา, ธนวัฒน์ (Princess of Naradhiwas University Journal, 2018)
Pellet mill is processed from rubber wood sawdust by flat die pellet mill. There are a D-type and a R-type. This research aimed to study the feed rate of rubber wood sawdust, the production rate of wood pellets, and the efficiency of wood pellet mill for converting rubber wood sawdust into pellets. The feed rate of rubber wood sawdust for D-type and R-type were 12 and 15 kg/h/kW-h, respectively. The production rate of wood pellets for D-type and R-type were 9.6 and 13.5 kg/h/kW-h, respectively. The R-type had a higher efficiency of 14%, compared with D-type.